Comparison of efficacy of eutectic mixture of local anaesthetic with amethocaine on pain during venipuncture among term neonates in a tertiary care hospital, India - Nair, Anagha M.; Prabakaran, Vetriselvi; Bethou, Adhisivam (International Journal of Contemporary Pediatrics, 2021)
Background: Neonates are frequently subjected to painful procedures which can adversely affect future pain perception. Pain control measures during invasive procedures include non-pharmacological and pharmacological methods. One pharmacological intervention that can be used prior to a needle insertion procedure is application of a topical local anaesthetic to numb the skin. Topical anaesthetics prevent nerve impulse transmission, promoting skin analgesia by acting on the free dermal terminations. This study compares the efficacy of eutectic mixture of local anaesthetic with amethocaine on pain during venipuncture among term neonates. Methods: A randomized clinical trial was conducted with 70 term neonates who underwent venepuncture in neonatal intensive care unit of a tertiary care centre. A simple random sampling technique was used to enrol the neonates who met the inclusion criteria. Neonatal infant pain scale was used to collect the data. Descriptive and inferential statistics were used to analyse the data. frequency and percentage were used to describe the clinical and demographic variables of the study participants. The efficacy of topical local anaesthetics was analysed using independent student t test. Chi-square test was used to identify the association of level of pain with clinical and demographic characteristics of the neonate. The analysis was done with SPSS 21st version. Results: Compared to amethocaine group, in eutectic mixture of local anaesthetic (EMLA) group only lesser number of neonates experienced severe level of pain and mild to moderate level of pain. Though mean pain score in EMLA group (3.457±1.633) was lesser than amethocaine group (4.000±1.514) it was not significant (p=0.347). Conclusions: The study revealed the efficacy of topical anaesthetics in relieving pain in term neonates during venipuncture.